DOI: 10.11606/t.89.2007.tde-22022008-144726
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados ao risco cardiovascular em mulheres no climatério

Abstract: A todas as mulheres, pacientes destes ambulatórios, que aceitaram fazer parte desta pesquisa. A todos os funcionários da Faculdade de Saúde Pública/USP, em especial à Iara Macedo, Meirezilda Ap. Soares e Souza, Elisabeth Teobaldo dos Santos, Elisabete Araújo Cheffer Pires e Renilda M. de Figueiredo Shimono. Aos funcionários da Biblioteca da Faculdade de Saúde Pública da USP que, por sua pronta disposição em nos auxiliar, são parte de todos os trabalhos desenvolvidos nesta escola. À Seção de pós-graduação do PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 90 publications
0
3
0
3
Order By: Relevance
“…Among 223 HIV-infected individuals aged 20-59 from the city of São Paulo, the prevalence of central obesity was 45.7%, with women having a higher prevalence of abdominal obesity and overweight status when compared to men, coinciding with the results of this study 7 , 27 . The author also cites previous studies with patients treated using protease inhibitors showing that the accumulation of fat is often higher among women 12 , 15 . Also, the development of male body patterns has been reported in most women with LLS 15 , 20 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Among 223 HIV-infected individuals aged 20-59 from the city of São Paulo, the prevalence of central obesity was 45.7%, with women having a higher prevalence of abdominal obesity and overweight status when compared to men, coinciding with the results of this study 7 , 27 . The author also cites previous studies with patients treated using protease inhibitors showing that the accumulation of fat is often higher among women 12 , 15 . Also, the development of male body patterns has been reported in most women with LLS 15 , 20 .…”
Section: Discussionmentioning
confidence: 85%
“…According to the American Dietetic Association, anthropometry has been widely used to assess the health and nutritional status of individuals, communities or populations, not only due to its simplicity and low cost, but also because it can provide an approximation of body composition and distribution of body fat 1 , 15 , 18 . The aim of this study was to assess the prevalence of self-reported lipoatrophy/lipohypertrophy and nutritional status by anthropometric measurements in patients with HIV/AIDS in a cohort of outpatient HIV-infected persons in São Paulo, Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar do IMC seja utilizado na maioria dos estudos populacionais, devido à facilidade na obtenção dos valores de peso e estatura, não possibilita a avaliação da composição corporal. Deste modo, observa-se, aumento do interesse em medidas que discriminem melhor a quantidade de gordura corporal, bem como sua relação associada à obesidade, pois o IMC fornece um quadro incompleto da magnitude do risco cardiovascular associado à obesidade, uma vez que ele não identifica as pessoas com obesidade abdominal (71,72,73,74) .…”
Section: Resultsunclassified
“…Estudo realizado por França (142) revelou que maior paridade significou risco cardiovascular aumentando, segundo obesidade global mensurada pelo IMC e pelo percentual de gordura corporal, em mulheres que apresentaram, em média, 2,5 partos. Dado semelhante, quanto à paridade, foi encontrado nesta amostra, onde as entrevistadas referiram, em grande maioria, ter tido entre um e dois partos, dentre estas, 54,54% das mulheres com lipodistrofia e uso da HAART, 44,44% das que usam HAART, mas não têm lipodistrofia e 45,83% do grupo que não faz uso da HAART.…”
Section: Pesquisadores Do Dad (Data Collection On Adverse Events Of Aunclassified
“…Deste modo, observa-se, na literatura, aumento do interesse em medidas que discriminem melhor a quantidade de gordura corporal, bem como sua relação associada à obesidade, pois o IMC fornece um quadro incompleto da magnitude do risco cardiovascular associado à obesidade, uma vez que ele não identifica as pessoas com obesidade abdominal (113,142,171,174) . (123) , onde a análise da composição corporal pelo BIA indicou que as meninas de sua amostra de soropositivos apresentaram maiores índices de adiposidade quando comparado aos meninos.…”
Section: Imc<19 E O Estudo Do Nhanes -National Health and Nutrition Eunclassified